Primary cutaneous aspergillosis in an immunocompetent individual - Tamta, Aatish; Singdia, Heena; Dhakar, Monesh; Kothari, Deepika; Bhargava, Puneet; Mathur, Deepak K. (International Journal of Research in Dermatology, 2022)
Aspergillosis is an uncommon fungal infection in which primary cutaneous sites are very rare. Most cases occur in immunocompromised patients and infection in immunocompetent patients, is extremely rare, but an increase in prevalence has been noted in last 20 years. A case of primary cutaneous aspergillosis (PCA) in a 40-year-old immunocompetent shopkeeper resident of Jaipur Rajasthan presenting with verrucous growth on the lower lip has been reported in this case study.